A new species of Pestalotiopsis from leaf spots of Licuala grandis from Hainan, China - Geng, Kun; Zhang, Bin; Song, Yu; Hyde, Kevin D.; Kang, Ji-Chuan; Wang, Yong (Phytotaxa, 2013)
A new species, Pestalotiopsis licualacola, was isolated from grey leafspots of Licuala grandis (ruffled fan palm). It is morphologically distinct in having relatively small, greyish brown conidia (16–20 × 3–5 μm), and 1–3 short apical appendages without knobs. Phylogenetic analysis based on combination of ITS, β-tubulin and tef1 gene sequence data clearly distinguishes P. licualacola from other species in this genus, with ex-type sequence data in GenBank. Based on morphology and molecular phylogeny we describe it as a new species.